The Distribution of Tenant Benefits in Public Housing - Murray, Michael P. (Econometrica, 1975)
In this paper we estimate the Hicksian equivalent variation of consumer's surplus for a sample of public housing tenants and examine the distribution of these surpluses by household characteristics. To do this we estimate the parameters of a generalized CES utility function (imposing second order constraints as needed) and of a Cobb-Douglas utility function. The Cobb-Douglas specification is rejected statistically and benefit estimates based on it follow a significantly different distributional pattern than those estimated with the generalized CES, although there is not much difference in average benefits.